The Effectiveness of Student Worksheet Based on Scientific Literacy to Train Argumentation Skills on Factors that Affecting Reaction Rate - Nirmala Puteri Batari; Rusmini Rusmini (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study purposes to determine the effectiveness of scientific literacy-based worksheets to practice students' argumentation skills on the factors that affect the rate of reaction. The variables of this study were argumentation skill and science literacy. Subject and population of this study were 35 student of class XI IPA at SMAN 12 Surabaya. The analysis of this study used the N-gain and statistical tests including the Wilcoxon test and the Spearman test. The effectiveness of Student Worksheet was stated to be very effective in terms of the scientific literacy test with N-Gain score of 0.7 in the high category and an argumentation test with N-Gain  score of  0.8 in the high category. Supported by the Wilcoxon test with acceptance of H1 which showed an average difference in scientific literacy and argumentation before and after treatment, and the Spearman correlation test gets an rho of 0.873 which indicates a strong relationship between literacy and argumentation.